Volcano multiparameter monitoring system based on Internet of Things (IoT) - Hidayatullah, Nur Asyik; Putra, Rakhmad Gusta; Atmaja, Ardian Prima; Sudirman, Dirvi Eko Juliando; Faizin, Kholis Nur; Subkhan, Muhamad Fajar; Kalam, Akhtar (Australian journal of electrical & electronics engineering, 2020)
Indonesia is an archipelagic country that lies within the Circum-Pacific belt or the Ring of Fire. Currently, the country hosts 127 active volcanoes, of which only 69 are properly monitorable for the activity around the clock. In light of volcanic disaster risk reduction and early warning system, volcano monitoring becomes indispensable. Since volcanoes have steep terrestrial contour and vast area, plenty of monitoring points are thus necessary. The higher the number of the monitoring points, the more costly it will be to procure the instruments required for the volcano monitoring. Therefore, it requires monitoring devices that are effective and efficient. This paper presents an application monitoring for active volcano using Wireless Sensor Network (WSN) and Internet of Things (IoT). Our main goals were to create low power consumption monitoring systems that are easy to maintain, easy to deploy, energy-saving, flexible and integrated. The wireless communication system on this device uses the IEEE 802.15.4 standard. Finally, this paper demonstrates the applicability of the proposed system for the detection of volcanic multi parameters such as Carbon Monoxide (CO), Hydrogen Sulphide (H2S), Crater Temperature, pH and Seismic.